Analisis Isu Mental Health Terhadap Kinerja Pekerja pada Generasi Z di Provinsi Sumatera Utara dan Aceh - Febriani Berutu; Muhammad Rahmat Hidayat; Rusdi Rusdi (Indo Publishing, 2026)
This study aims to analyze the effect of stress on the mental health of Generation Z workers in Sumatera Utara and Aceh Provinces, as well as to examine the role of vigor at work as a mediating variable and compare the results across the two provinces. This study used a quantitative approach with a survey method by distributing questionnaires to 544 Generation Z worker respondents in both provinces. The results were tested using SPSS software and statistically analyzed using path analysis and the Sobel test to examine the direct and indirect effects between variables and the mediating role of vigor at work. The results showed that in Sumatera Utara Province, stress had a direct negative effect on mental health (β = –0.165) and on vigor at work (β = –0.179), while vigor at work had a positive effect on mental health (β = 0.698). The indirect effect of stress on mental health through vigor at work was –0.125, bringing the total effect of stress on mental health to –0.290. The Sobel test yielded a Z value of –2.93 > 1.96 in absolute terms, indicating that vigor at work significantly mediates the relationship between stress and mental health in Sumatera Utara Province. In Aceh Province, the study showed that stress had no significant effect on mental health (β = –0.066) or vigor at work (β = –0.064), while vigor at work remained positive on mental health (β = 0.701). The indirect effect of stress on mental health through vigor at work was –0.044, with a total effect of –0.110. The Sobel test yielded a Z value of –1.06 < 1.96 in absolute terms, indicating that vigor at work did not significantly mediate the relationship between stress and mental health in Aceh Province.